Removal of manganese (II) from drinking water by aeration process using an airlift reactor. (April 2017) - Kouzbour, Sanaa; El Azher, Nisrine; Gourich, Bouchaib; Gros, Fabrice; Vial, Christophe; Stiriba, Youssef
Highlights: Manganese removal from water by oxidation through aeration process has been studied. Manganese oxidation follows a pseudo-first-order with respect to Mn 2+ and OH − ions. Oxidation is not limited by oxygen mass transfer and is catalyzed by MnO2 particles. The kinetics of the homogeneous and heterogeneous mechanisms have been estimated. A model predicting the rate of manganese oxidation has been established. Abstract: The objective of this study is the removal of soluble manganese Mn(II) from drinking water by aeration process in order to oxidize it into insoluble manganese dioxide MnO2 using a Split-Rectangular Airlift Reactor (SRAR). The description of the global hydrodynamics, liquid mixing and gas-liquid mass transfer properties of the SRAR were presented in previous works and were compared to data and correlations in the literature. The effects of operating conditions were investigated, including initial pH, Mn(II) concentrations and amount of MnO2 particles. The major findings are that the oxidation of Mn(II) corresponds to a kinetically-slow reaction that is strongly pH-dependent. The kinetic data show an autocatalytic behaviour due to the oxidation of Mn(II) on the MnO2 surface, which allows the conversion to go to completion. This behaviour is confirmed by the addition of MnO2 fine particles that increase drastically the reaction rate. At high initial Mn(IV) concentrations, the kinetic law was shown to be pseudo-first order in Mn(II), with an apparent kinetic constant depending on the initial amount of Mn(IV) compounds. This constant was fitted by a linear model as a function of Mn(IV) concentration. This model was shown to be in good agreement with experimental data. Comparing with other techniques, aeration is an efficient process because it gives us a removal efficiency of 90% in less than 40 min at pH 9.5 and initial soluble Mn(II) and insoluble Mn(IV) concentrations between 5 and 20 and 0–500 mg/L, respectively, while avoiding the drawbacks of strong oxidizers and biological oxidation processes. A model able to predict quantitatively Mn removal as a function of pH, initial Mn(II) and initial Mn(IV) concentrations is also developed.